On the Attack by Alcohol on One Carbon-Carbon Double Bond of Dichloro(Norbornadiene)Palladium(II) - Raymond Roulet; Raymond Vouillamoz; Umberto Belluco; Mauro Graziani (CHIMIA)
The kinetics of nucleophilic attack by alcohol on one double bond of PdCl2(nbd) (nbd = 2,5-norbornadiene) has been studied by UV spectrophotometry. In dichloromethane the dichlorocomplex is only slightly solvolysed, but is in equilibrium with 4-coordinated PdCl3(nbd)- when chloride is added to the solution. Both species react with alcohol and the overall mechanism is complicated, the direct attack of the double bond being only one of the parallel paths. Direct addition of methanol was unambiguously shown to exist in the case of [Pd(dipyridyl)(C8H12)](PF6)2 (C8H12 = 1,5-cyclooctadiene)where the two positions cis to the diolefin are blocked by the chelated 2,2 '-dipyridyl.